2014
DOI: 10.13171/mjc.2.5.2014.05.01.22
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites and antioxidant activity of seed extracts from Solanum elaeagnifolium Cav.

Abstract: The aim of this study was to screen various solvent extracts of seeds of Solanum elaeagnifolium to display the phytochemical composition, the total phenolic content, the total flavonoid content and the antioxidant capacity in order to find possible sources for future novel antioxidants in food and pharmaceutical formulations. Various extracts of seeds of Solanum elaeagnifolium were obtained by maceration. The total phenolic content of the different extracts was determined by Folin-Ciocalteu method, and the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Several previous studies have shown that wild Solanaceae species may be useful as potential sources of bioactive molecules and biocontrol agents (Feki et al. ; Santhanam et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have shown that wild Solanaceae species may be useful as potential sources of bioactive molecules and biocontrol agents (Feki et al. ; Santhanam et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Although S. elaeagnifolium was considered as a potential threat to thousands of hectares of Tunisian irrigated fields in arid and semiarid regions (Mekki ), it has been identified as potent sources of secondary metabolites (Feki et al. ) and candidates for biological control (Cuda et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction yield of S. elaeagnifolium depended on the extraction solvents and the plant part. Feki et al [36] collected the S. elaeagnifolium plant (for seed study) in December 2011 (final maturity stage) in Monastir. They found the methanol extract of S. elaeagnifolium seeds presented the highest yields at 7.7%, followed by the acetone extract at 5.31%.…”
Section: Yield Of Extractsmentioning
confidence: 99%